Modern Slavery: A Study of “Bilal: A New Breed of Hero” - Zahrho, Nur Shofiyyah; Wahyudi, Jarot (Insaniyat : Journal of Islam and Humanities, 2024)
Slavery has been a tradition from the Jahiliyyah era to the present. The film “Bilal A New Breed of Hero”, tells the story of the Arab Jahiliyyah model of slavery which can be used as a lesson in the toughness of a Bilal who is eventually crowned a hero. Even though this film tells of slavery in the past, the main message of this film is the desire to eradicate slavery from the face of the earth which can be used as a valuable lesson now and in the future. This paper is dedicated to examining the film “Bilal A New Breed of Hero” from the aspect of its content and main messages that are still relevant today. The issue of slavery still occurs in the modern era, only in different forms and models. This topic is interesting to study because the issue of slavery is still being discussed in various forums and media. The method used in this research is content analysis. Finally, the researcher found that there were 3 categories of data as follows, 3 data which described the beginning of Bilal and Ghufairah as slaves, 3 data which described the slave trafficking, and 8 data which described the treatment of masters towards slaves.